2023
DOI: 10.3390/ijerph20021072
|View full text |Cite
|
Sign up to set email alerts
|

The Influencing Effect of Tourism Economy on Green Development Efficiency in the Yangtze River Delta

Abstract: In the context of ecological priority and green development strategy, accelerating the upgrading of tourism structure and promoting the development of ecotourism is an important guarantee to achieve green and low-carbon economic growth and high-quality development. On the basis of constructing comprehensive evaluation indicators of tourism development (TD) and green development efficiency (GDE), this study analyzed the impulse response relationship between TD and GDE and the impact effect of TD on GDE in the Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This study resolves this disagreement and finds that, within one region, the impact of the TDI on the ERI can be both positive and inhibitory, which mainly stems from the differences in the direction of tourism development in tourist destinations. Tourism destinations that prioritize ecological impacts, supported by the concept of sustainable development, see a positive impact of the TDI on the ERI [87,89]. On the contrary, the TDI has a dampening effect on the ERI in certain tourist places that only emphasize the expansion of the tourism economy while neglecting ecological and environmental protection [84,87].…”
Section: Discussionmentioning
confidence: 99%
“…This study resolves this disagreement and finds that, within one region, the impact of the TDI on the ERI can be both positive and inhibitory, which mainly stems from the differences in the direction of tourism development in tourist destinations. Tourism destinations that prioritize ecological impacts, supported by the concept of sustainable development, see a positive impact of the TDI on the ERI [87,89]. On the contrary, the TDI has a dampening effect on the ERI in certain tourist places that only emphasize the expansion of the tourism economy while neglecting ecological and environmental protection [84,87].…”
Section: Discussionmentioning
confidence: 99%
“…The performance or development level of SECR is calculated by using the entropy weight method. The entropy weighting method is widely used to evaluate comprehensive development level [ 16 , 24 , 38 ]. The information entropy is used in this method to reflect the amount of information obtained for weighting [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Xie et al used a spatial measurement model to study the direct and spillover effects of financial agglomeration on the GEE of Chinese cities and hypothesized that financial agglomeration may improve GEE, but it had a negative spillover effect on the GEE of neighboring cities [ 55 ]. Hu et al examined the impact of tourism economy on GEE and found that it had a significant inverted U-shaped impact on the GEE [ 56 ]. Based on the data of 278 Chinese cities, Liu and Dong used a spatial econometric model to analyze the relationship between technological innovation and GEE and found that technological innovation had positive direct and indirect effects on GEE [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%